Effect of co2 partial pressure on dry reforming of ethanol for hydrogen production - Fayaz, Fahim; Ahmad Ziad, Sulaiman; Singh, Sharanjit; Akbari, Sweeta (International Journal of Innovative Research and Scientific Studies, 2018)
The effect of CO2 partial pressure on ethanol dry reforming was evaluated over 5%Ce-10%Co/Al2O3 catalyst at = PCO2 = 20-50 kPa, PC2H5OH = 20 kPa, reaction temperature of 973 K under atmospheric pressure. The catalyst was prepared by using impregnation method and tested in a fixed-bed reactor. X-ray diffraction measurements studied the formation of Co3O4, spinel CoAl2O4 and CeO2, phases on surface of 5%Ce-10%Co/Al2O3 catalyst. CeO2, CoO and Co3O4 oxides were obtained during temperature–programmed calcination. Ce-promoted 10%Co/Al2O3 catalyst possessed high BET surface area of 137.35 m2 g-1. C2H5OH and CO2 conversions was improved with increasing CO2 partial pressure from 20-50 kPa whilst the optimal selectivity of H2 and CO was achieved at 50 kPa.